Comedian Mathematical Thinking: An Islamic Examination of Inductive, Deductive, and Analogy Approaches in the Creation of Stand-Up Comedy Material - Aji, Fauzan Bayu; Nurmalitasari, Dewi; Lestari, Andika Setyo Budi; Muhammad, Ilham (Assyfa Journal of Islamic Studies, 2023)
This study examines the thinking process of comedians in creating Stand-Up Comedy material and highlights the similarities between comedy structures and mathematical thinking. Incorporating comedy structures into classroom learning can create a fun and engaging atmosphere while effectively conveying concepts and achieving learning objectives. Stand-Up Comedy, as a solo performance, allows comedians to present their material independently (Utami, 2018). In line with an Islamic perspective, this study aims to explore how the comedian's mathematical thinking process aligns with the inductive, deductive, and analogical methods, while considering the values and principles of Islam. By analyzing the intersection of humor, mathematics, and Islamic teachings, this research seeks to provide insights into utilizing comedy techniques to enhance teaching and learning experiences, promoting an inclusive and enjoyable educational environment that respects Islamic values and objectives.